Determining the maternal attitude in supporting infant development (Annals of Medical Research, 2023)
Aim: The positive contribution of parental support to children's cognitive, emotional and social development in early infancy is well known. The aim of this study was to learn the attitudes and opinions of mothers of newborns about supporting development, shared reading, playing games and watching television and to evaluate the factors that may affect these predictions.Materials and Methods: The study was conducted with 154 mothers who applied to İnönü University Faculty of Medicine Developmental Paediatrics outpatient clinic using the "Maternal Attitude Interview Form Regarding Supporting Infant Development".Results: Findings revealed that 136 (88.3%) of mothers planned to reading together, but 88 (57.1%) of them didn’t plan to start before the age of 1 year. There were no baby books in 45.5% and no toys in 30.5% of the houses. A total of 20.1% of the mothers believed that watching television would have a positive impact on development, while 37% planned to allow their children to watch television before the age of 2 years. According to the regression analysis, it was determined that the most significant factor influencing mothers' intention to begin reading books with their babies before the age of 1 year was higher level of education (p
Keywords: Maternal attitude; Early childhood; Parenting; Developmental support; Shared reading